PRODUCTIVE CHAIN OF BOLAINA BLANCA (GUAZUMA CRINITA MART.) IN LEONCIO PRADO PROVINCE - Puerta, Ronald (2022)
The objective of this paper is to describe the links in the value chain of the bolaina blanca (Guazuma crinita Mart.) in the Leoncio Prado province, Peru. For this, available information was reviewed, as well as visits to the fi eld andto institutions to learn about the forestry activity directly related to the Bolaina blanca. As a result, it was possible to verify that the white bolaina plantations have been established using traditional planting methods, the use and transformation of the wood is quite precarious, while the commercialization is carried out at a regional and national level, however, despite the little The industrialization of wood represents great potential for the reactivation of the post-pandemic local economy within a favorable regulatory framework.